The strategies of China's firms : resolving dilemmas - Yang, Hailan; Morgan, Stephen L.; Wang, Ying; ScienceDirect eBooks (Waltham, MA : Chandos Publishing is an imprint of Elsevier, 2015)
This book aims to analyze how China's firms in the consumer electronics (CE) sector have developed their business strategy and corporate governance during the reform process. This book examines the CE sector in particular because it is one of the country's most important and dynamic manufacturing sectors and one of the earliest market-oriented sectors.
Online resource; title from PDF title page (Ebsco, viewed July 30, 2015).
Includes bibliographical references and index.
Elsevier
Keywords: Corporate governance -- China; Business enterprises -- China; China -- Economic policy; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business enterprises; Corporate governance; Economic policy; China; Electronic books